2020
DOI: 10.1007/s11101-020-09673-w
|View full text |Cite
|
Sign up to set email alerts
|

A critical review: traditional uses, phytochemistry, pharmacology and toxicology of Stephania tetrandra S. Moore (Fen Fang Ji)

Abstract: Stephania tetrandra S. Moore (S. tetrandra) is distributed widely in tropical and subtropical regions of Asia and Africa. The root of this plant is known in Chinese as ''Fen Fang Ji''. It is commonly used in traditional Chinese medicine to treat arthralgia caused by rheumatism, wet beriberi, dysuria, eczema and inflamed sores. Although promising reports have been published on the various chemical constituents and activities of S. tetrandra, no review comprehensively summarizes its traditional uses, phytochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 260 publications
(343 reference statements)
0
30
0
Order By: Relevance
“…Based on these results, the authors suggested that mixing vitamin C with diammonium glycyrrhizinate could be a promising strategy for the treatment of severe COVID-19 symptoms [301]. Further, several studies endorsed the definite clinical effect of traditional Chinese medicine (TCM), in which the glycyrrhizin or licorice extract is used, for COVID-19 treatment [302]. Ursodeoxycholic acid (UDCA) is a hydrophilic epimer of chenodeoxycholate that demonstrated the ability to stimulate alveolar fluid clearance in lipopolysaccharide-induced pulmonary edema, leading to an improvement of acute respiratory distress syndrome.…”
Section: Natural Compounds From Plants and Sars-cov-2mentioning
confidence: 99%
“…Based on these results, the authors suggested that mixing vitamin C with diammonium glycyrrhizinate could be a promising strategy for the treatment of severe COVID-19 symptoms [301]. Further, several studies endorsed the definite clinical effect of traditional Chinese medicine (TCM), in which the glycyrrhizin or licorice extract is used, for COVID-19 treatment [302]. Ursodeoxycholic acid (UDCA) is a hydrophilic epimer of chenodeoxycholate that demonstrated the ability to stimulate alveolar fluid clearance in lipopolysaccharide-induced pulmonary edema, leading to an improvement of acute respiratory distress syndrome.…”
Section: Natural Compounds From Plants and Sars-cov-2mentioning
confidence: 99%
“…Papaverine modulated the activity of Th17 by reducing the expression of NF-κB, p38MAPK, RANKL, and IL-23 16 . The tetrandrine in Stephania tetrandra can suppress antibody synthesis by B cells and the mitogeninduced lymphoproliferative response, inhibiting activation of human peripheral blood T-cells 17 .…”
Section: Immunomodulatory Activity Of Secondarymentioning
confidence: 99%
“…Currently, platforms for high throughput screening of compounds, together with stringent functional and safety validations are used to better understand the mechanisms of action of functional compounds. Concordantly, for the development of novel therapeutic drugs from TCM-derived herbs, a similar approach was established (Martel et al, 2017a ; Jiang et al, 2020 ). Through this method, many active components in TCM herbs were identified.…”
Section: Introductionmentioning
confidence: 99%